The Mortlach Phase - Walde, Dale Allen (University of Calgary, 1994)
Bibliography: p. 175-194. This dissertation has re-examined the latest precontact/early contact archaeological assemblages of southern Saskatchewan and related materials in northeastern Montana, northwestern North Dakota, and southwestern Manitoba. The Mortlach Phase, first proposed by Joyes (1973) and often questioned by other investigators, is redefined and offered again to the archaeological community. This phase is divided into two contemporaneous sub-phases (Lozinsky and Lake Midden) on the basis of differences in external social relationships reflected by participation in different lithic raw material exchange systems and the presence of different "foreign" pots in the two subphases. The northern Lozinsky Sub-phase has strong evidence of interaction with Selkirk peoples of the boreal forest in central to northern Saskatchewan while the southern Lake Midden Sub-phase demonstrates interaction with Middle Missouri village peoples. Written records, artifact decoration, and archaeological data are used to support a contention that the Mortlach Phase people were ancestors of Assiniboine peoples. Locations of the Lozinsky and Lake Midden Subphases are demonstrated to coincide with those of ethnographically known northern and southern subdivisions of Saskatchewan Assiniboine groups.